2019
DOI: 10.1042/bsr20182254
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus bulgaricus improves antioxidant capacity of black garlic in the prevention of gestational diabetes mellitus: a randomized control trial

Abstract: Objectives: Lactobacillus bulgaricus may improve antioxidant capacity of black garlic in the prevention of gestational diabetes mellitus (GDM).Methods: Black garlic was prepared with or without L. bulgaricus. Volatile and polysaccharides were analyzed by using LC-MS, Fourier Transform infrared (FTIR) and 13C nuclear magnetic resonance (NMR). The study design was parallel randomized controlled trial and 226 GDM patients were randomly assigned into BG (black garlic and L. bulgaricus) and CG (black garlic) groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
(70 reference statements)
0
8
0
1
Order By: Relevance
“…For example, Lactobacillus interacts with many pathogens by secreting salivary hormone B (an antibiotic) [ 44 ]. Other studies have found that the fermentation of lactic acid bacteria can not only enhance the physiological activity of intestinal peristalsis, but also improve immunity and avoid hyperglycemia [ 45 , 46 ]. Bifidobacterium is also a beneficial bacteria in the intestinal tract, and it has immuno-modulation and hypoglycemic effects [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lactobacillus interacts with many pathogens by secreting salivary hormone B (an antibiotic) [ 44 ]. Other studies have found that the fermentation of lactic acid bacteria can not only enhance the physiological activity of intestinal peristalsis, but also improve immunity and avoid hyperglycemia [ 45 , 46 ]. Bifidobacterium is also a beneficial bacteria in the intestinal tract, and it has immuno-modulation and hypoglycemic effects [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lipid peroxidation metabolite MDA can damage biological macromolecules such as proteins and nucleic acids, causing the body to age and develop various diseases. The level of MDA indirectly reflects the degree of free radical attack on the body cells, and it is another important indicator of the degree of oxidative damage in the body ( Si et al, 2019 ). Reducing the MDA content in tissues and serum are of great significance to alleviate oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lee et al [99] observed that aged garlic extract significantly decreased thiobarbituric acid reactive substances levels and elevated the activities of SOD, glutathione peroxidase (GSH-Px), and catalase (CAT) in diabetic mice. The results obtained by Si et al [100] demonstrated that 40 weeks of supplementation of BG lowered the levels of plasma malondialdehyde, SOD, GSH-Px, and total antioxidant capacity in pregnant women. They also mentioned that Lactobacillus bulgaricus improved the antioxidant capacity of BG in the prevention of gestational diabetes mellitus.…”
Section: Effects Of Black Garlic On Metabolic Disorders 611 Black Garlic and Diabetes Mellitusmentioning
confidence: 96%